PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAME TOURNAMENT (TGT) TERHADAP KERJASAMA DAN KETERAMPILAN BERMAIN SISWA PADA PERMAINAN SEPAKBOLA MINI DALAM PEMBELAJARAN PENDIDIKAN JASMANI - Rinaldy Ardiansyah, - (2019)
Tujuanpenelitianiniadalahuntukmengetahuipengaruh model pembelajarankooperatiftipeTeams Game Tournament (TGT) terhadaphasilketerampilanbermainsepakboladankerjasamasiswaSMP YayasanAtikanSunda.Metodepenelitianex-pose-fakto. Penelitiandilaksanakanterhadap 40 siswaSMP YayasanAtikanSunda.Instrumen yang digunakanadalah tes Game Performance AssesmentInstrument(GPAI) dan kuesioner tentang kerjasama. Berdasarkan hasil perhitungan uji independent sample t test diperoleh nilai sig = 0,005 untuk keterampilanbermainsepakbola dan nilai sig. = 0,000 untuk kerjasama, sehingga nilai sig. baik keterampilanbermainsepakbola dan kerjasama< 0,025 jadi Ha diterima. Kesimpulanbahwasanya model pembelajarankooperatiftipe TGT memberikanpengaruhpositifterhadapketerampilanbemainsepak bola mini dankerjasamasiswaSMP YayasanAtikanSunda. Kata kunci :modelpembelajarankooperatif, Teams Game Tournament (TGT), keterampilanbermainsepakbola mini, kerjasama.   ABSTRACT RinaldyArdiansyah (1205702) "THE INFLUENCE OF COOPERATIVE LEARNING MODEL OF TEAMS GAME TOURNAMENT (TGT) TOWARDS COOPERATION AND SKILLS OF STUDENTS PLAYING IN MINI SOCCER GAMES IN LEARNING OF JASMANI EDUCATION IN ATIKAN SUNDA FOUNDATION JUNIOR HIGH SCHOOL " The purpose of this study was to determine the effect of the Team Game Tournament (TGT) type of cooperative learning model on the results of football playing skills and cooperation between AtikanSunda Foundation Middle School students. Ex-pose-facto research method. The study was conducted on 40 AtikanSunda Foundation Middle School students. The instrument used was the Game Performance Assessment Instrument (GPAI) test and a questionnaire about collaboration. Based on the results of the calculation of the independent sample t test, the value of sig = 0.005 was obtained for football playing skills and the value of sig. = 0,000 for cooperation, so the value of sig. both football playing skills and cooperation <0.025 so Ha was accepted. The conclusion is that the TGT type of cooperative learning model has a positive influence on the skills of mini soccer players and the cooperation of AtikanSunda Foundation Junior High School students. Keywords: cooperative learning model, Team Game Tournament (TGT), mini soccer playing skills, collaboration